Role of Firm Size and Profitability on Capital Structures and Its Impact Over Firm Value - Sudrajat, Jajat; Setiyawati, Hari (Dinasti Publisher, 2021)
This research has a purpose to reveal and evaluate the significant impact from firm size to capital structure; Profitability to capital structure; capital structure to firm value; firm size to firm value; profitability to firm value; and those indirect effects of firm size and capital structure towards firm value; and those indirect effects of profitability along with capital structure to firm value. This research population was 178 manufacturing companies, while the research sample was 13 automotive subsector companies and its components which registered on the IDX by the sampling technique were purposive sampling methods. The research method that was used was quantitative methods, while the analysis model used regression analysis model with t-test and sobel test. These research results illustrated that firm size had a significant affect on capital structure; profitability had a negative and significant affect on capital structure; capital structure has no significant affect on firm value. firm size had a significant affect on firm value; profitability has no effect and is insignificant to firm value; there is no indirect and insignificant affect occurred between firm size, capital structure and firm value; There is no indirect and insignificant affect that occurs between profitability, capital structure and firm value.